2008
DOI: 10.1021/jp7119685
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of WSe2 Nanoparticles and Carbon Nanotubes

Abstract: A single-step, nonaqueous, solventless, facile chemical reaction is carried out to synthesize a WSe 2 nanoparticles/carbon nanotubes [WSe 2 /C] composite at moderate temperature. The use of highly toxic H 2 Se gas is avoided, reacting elemental selenium powder with W(CO) 6 at 750 °C under their autogenic pressure in a closed reactor. Without further processing the as-prepared WSe 2 /C nanocomposite, detailed characterizations are carried out, and a proposed reaction mechanism is discussed. X-ray diffraction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Furthermore, the MoS 2 or MoSe 2 nanoflakes inclusion38 with carbon is synthesized by thermal (750 °C) reaction between Mo(CO) 6 and S or Se at their autogenic pressure in a closed reactor under inert atmosphere. Likewise, WSe 2 /C nanofibers39 are fabricated during a 1 h chemical reaction between W(CO) 6 and Se at 750 °C in the dry autoclave. The SEM (Figure 1d) presents the carbon fibers with 50–100 nm diameters and several micrometers lengths with globular WSe 2 nanofibers 39.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the MoS 2 or MoSe 2 nanoflakes inclusion38 with carbon is synthesized by thermal (750 °C) reaction between Mo(CO) 6 and S or Se at their autogenic pressure in a closed reactor under inert atmosphere. Likewise, WSe 2 /C nanofibers39 are fabricated during a 1 h chemical reaction between W(CO) 6 and Se at 750 °C in the dry autoclave. The SEM (Figure 1d) presents the carbon fibers with 50–100 nm diameters and several micrometers lengths with globular WSe 2 nanofibers 39.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach involves only the metallic tungsten, S or Se powders. Although Pol et al had demonstrated the synthesis of WS 2 breeds embedded in carbon and WSe 2 /C nanocomposite by the reaction of W(CO) 6 with S or Se under RAPET conditions at 750°C for 3 h. (Pol et al 2007(Pol et al , 2008. Our approach yields WS 2 and WSe 2 product without carbon.…”
Section: Hrsem Measurementsmentioning
confidence: 87%
“…The current methods used to prepare the WS 2 and WSe 2 as thin films on a variety of substrates are DC and RF sputtering method (Regula et al 1996;Ellmer et al 1997), sulfurization of ion beam sputtered WO 3 thin films (Genut et al 1992;Ennaoui et al 1997), pulse laser deposition (Zabinski et al 1994), vapor deposition method (Huang et al 2014), electrodeposition (Devadasan et al 2001), chemical bath deposition (Chatzitheodorou et al 1988). Pol and his coworkers had demonstrated the synthesis of WS 2 breeds embedded in carbon and WSe 2 /C nanocomposite by employing the RAPET technique (Pol et al 2007(Pol et al , 2008). In the current article, the synthesis of WS 2 and WSe 2 nanocrystals with novel flower-like pattern of radially aligned nanoflakes via a RAPET method is demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports on 0D WSe 2 nanomaterial‐based gas sensors, but it has been synthesized for other applications like sodium and lithium ion batteries. Pol et al used a single‐step, nonaqueous, solvent less, facile chemical synthesis route (by reacting elemental selenium powder with W(CO) 6 at 750 °C under their autogenic pressure in a closed reactor) to prepare WSe 2 nanoparticles directly on carbon nanotubes surface 86. In another attempt, Zhang et al prepared WSe 2 nanoparticle coated carbon materials by a solid state reaction and used it as anode material for sodium‐ion batteries 87.…”
Section: Tungsten Chalcogenides and Their Gas Sensing Applicationsmentioning
confidence: 99%